ANALISIS HIDROKIMIA UNTUK INTERPRETASI SISTEM HIDROGEOLOGI DAERAH KARS - Taat Setiawan; Deny Juanda P.; Budi Brahmantyo; D. Erwin Irawan (Widyariset, 2010)
Cijulang and its surrounding area represent as karst morphology with the cavity network development as the result of groundwater dissolution process. The research of karst hydrogeology in Cijulang area was conducted by using hydrochemical analysis and compiled with the field hydrogeological observation data to identify the hydrogeological system. Based on hydrochemical analysis data as degree of acidity (pH), partial pressure of CO2 (Pco2), and saturation index of calcite (SIkalsit) that compiled with hydrogeological characteristics shown the change of groundwater flow mechanism on the spanning of certainly elevation. Diffusion flow mechanism happened at theelevation of 110–65 masl (transition zone-1) and then changed into conduit flow mechanism at the elevation of 65–35 masl (transition zone -2) and at the elevation of 35–20 masl (zone of continuous water circulation).